2013
DOI: 10.3390/ijms14035482
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidin Impedes Activity of Glutathione S-Transferase in the Midgut of Helicoverpa armigera Hübner

Abstract: Previous investigations have implicated glutathione S-transferases (GSTs) as one of the major reasons for insecticide resistance. Therefore, effectiveness of new candidate compounds depends on their ability to inhibit GSTs to prevent metabolic detoxification by insects. Cantharidin, a terpenoid compound of insect origin, has been developed as a bio-pesticide in China, and proves highly toxic to a wide range of insects, especially lepidopteran. In the present study, we test cantharidin as a model compound for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…It has been well demonstrated that insect GSTs are a superfamily of multifunctional enzymes that are involved in the detoxification of endogenous and xenobiotic compounds, including insecticides . The HZ16 strain has significantly higher GST activity than the Sus strain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well demonstrated that insect GSTs are a superfamily of multifunctional enzymes that are involved in the detoxification of endogenous and xenobiotic compounds, including insecticides . The HZ16 strain has significantly higher GST activity than the Sus strain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GSTs are synthesized with a detoxifying function because cantharidin could impede the GST catalytic activity of H. armigera (Khan et al. ). GSTs significantly increase the process of detoxification, as they possibly act as a binding protein with cantharidin and its analogues in a defence‐like response to toxicants (Bajsa et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Khan et al. ). Larvae that are exposed to Bt toxins exhibit a reduction in ACP, ALP and GST (Nathan et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kantaridin vyvolává apoptózu buněk a účinně aktivuje ERK-1/2, p38 a JNK u modelových buněčných linií U937 [42]. Inhibuje také rodinu enzymů zvaných glutathion S-transferázy [43], které katalyzují konjugaci redukovaného glutathionu s řadou hydrofobních látek, obsahujících elektrofilní centrum. Tyto enzymy hrají důležitou úlohu v detoxikaci různých xenobiotik.…”
Section: Farmakologie a Mechanismus Biologického účInku Kantaridinuunclassified